Biomechanical aging behaviour of clear aligners - Mei Li; Jin Carrol; Na Aishah; Marra Jamie; Guan Simon; Choi Joanne (Sciendo, 2024)
The biomechanical behaviour of clear aligners can affect the clinical efficacy of tooth movement.